Experiments and numerical simulations of Lueders bands and Portevin–Le Chatelier effect in aluminium alloy AW5083 - Mucha, M.; Rose, L.; Wcisło, B.; Menzel, A.; Pamin, J. (Archives of Mechanics, 2023)
This work is focused on the modelling of experimental behaviour of a bone-shape sample made of aluminium alloy AW5083 under tension. This behaviour involves propagating instabilities, namely Lueders bands and the Portevin–Le Chatelier effect. A series of experiments was performed at room temperature for three loading rates, showing the instabilities and failure. In the paper a large strain thermovisco-plasticity model is proposed and used for finite element simulations. This model contains initial softening and a hardening function based on the Estrin–McCormick concept to represent serrations and travelling shear bands. The issues of instability sources and regularisation are considered. The predictive capabilities of the model are examined. The proposed models are able to reproduce both Lueders bands and the PLC effect. Simulation results show good agreement with experiments regarding force–displacement diagrams and temperature levels.